1998
DOI: 10.1006/jsre.1998.5377
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Clinically Transplanted Muscles

Abstract: Backgrounds. Although a number of studies have examined the morphology and function of experimentally transplanted muscles, immunohistochemi-cal evaluation of clinically transplanted muscles has not been reported. The purpose of this study was to examine clinically transplanted muscles at long periods after transplantation with biochemical markers specific for satellite cell activation and muscle regeneration. Materials and Methods. Nine biopsies of muscles transplanted to the paralyzed face were examined. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…hypothesized that reinnervation had failed to occur in a few of their cases of human MNV muscle transfer, and that the flap had therefore atrophied. 18 In our study, however, despite obvious muscle innervation, muscle morphology was not fully restored in all cases. Moreover, the density of neural structures correlated with neither atrophy, function, nor any other particular parameters in our patient series.…”
Section: Muscle Atrophy and Innervationmentioning
confidence: 49%
See 4 more Smart Citations
“…hypothesized that reinnervation had failed to occur in a few of their cases of human MNV muscle transfer, and that the flap had therefore atrophied. 18 In our study, however, despite obvious muscle innervation, muscle morphology was not fully restored in all cases. Moreover, the density of neural structures correlated with neither atrophy, function, nor any other particular parameters in our patient series.…”
Section: Muscle Atrophy and Innervationmentioning
confidence: 49%
“…This finding is compatible with earlier observations on the continuation of muscle regeneration years after muscle transfer. 18 In our study, however, the activation of satellite cells was found to be time-dependent such that the longer the transferred muscle had been in its new site, the fewer were the attempts at regeneration. Satellite cell mitotic activity did not correlate with muscle fiber diameters of the flaps in our study, but there was a tendency for association (ns) between satellite cell activity and good function of the flap.…”
Section: Muscle Fiber Type Distributionmentioning
confidence: 80%
See 3 more Smart Citations